TEO-ANTROPOSENTRISME DALAM PARADIGMA HUKUM ISLAM: REORIENTASI FIKIH SOSIAL INKLUSIF - Muhammad Aulal Fikri Al-hasani; Abd. Muid N.; Kerwanto Kerwanto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2025)
In contemporary discourse, Islamic legal reasoning is often the primary focus of in-depth study. Philosophical studies of Islamic legal reasoning, especially the classical approaches, are often considered outdated by some contemporary thinkers. This argument arises because legal reasoning in the classical paradigm tends to be literalistic and static. As a result, the products of ijtihād in the classical paradigm often struggle to find relevance in the contemporary legal landscape. Therefore, it is crucial to seek a conception of Islamic legal reasoning that can integrate various fields of knowledge without marginalizing God's Sharia as the absolute authority. This is where theo-anthropocentrism becomes relevant. This research is a literature review on the concept of theo-anthropocentrism within the Islamic legal paradigm. As an analytical tool, the author employs integrative-interconnective theory as a basis for systematically constructing arguments. As a result, the principles of theo-anthropocentrism can, to a certain extent, become a new axis for progressive and inclusive Islamic legal reasoning. In its epistemological construction, theo-anthropocentrism emphasizes three core foundations. First, it places sacred texts as the primary object of study. Second, it considers various fields of knowledge holistically, including both religious and general sciences. Finally, it integrates these two dimensions harmoniously and comprehensively by emphasizing the principle of benefit (maslaḥah).